The Ancient Church at Megiddo: The Discovery and an Assessment of its Signficance - Adams, Edward (The expository times, 2008)
This article discusses the recently reported discovery of an ancient Christian structure at Megiddo in northern Israel and the controversy surrounding it. It begins with an account of the archaeological finds, in particular the mosaic floor and the inscriptions in it. A summary of the debate over dating follows, which focuses on the excavator's dating and the grounds on which it is reached, and challenges to that chronology. The rest of the article assesses the potential significance of the discovery at Megiddo for the archaeology of early Christianity, for the study of early ecclesiastical architecture, and for our knowledge of early Christian belief and Church life.